Scar-concealed 2 + 3 mm dual-port thoracoscopic sympathectomy for palmar hyperhidrosis: single-center outcomes - Yang, Qingjie; Li, Qingtian; Lv, Shenghua; Lan, Linhui; Liu, Ningquan; Wang, Mingyang; Sun, Xiaoyan; Han, Kaibao (Frontiers in Surgery, 2025)
ObjectiveTo minimize the trauma and incision of the operation for primary palmar hyperhidrosis (PPH), we have designed a inconspicuous scar thoracoscopic bilateral thoracic sympathetic chain transection via “2 + 3 mm” two-pinhole incisions (ISTTST). This study mainly retrospectively compares and analyzes the pros and cons of this surgical method vs. the conventional single-port thoracoscopic sympathetic nerve transection (CSTTST).MethodsData of patients with moderate or severe PPH and underwent thoracic sympathetic chain transection were collected. Patients undergoing ISTTST and those receiving CSTTST were included in the two-pinhole group and the single-port group respectively. The baseline characteristics, intraoperative and postoperative conditions of the two groups were compared.ResultsA total of 265 patients were enrolled, including 162 in the single-port group and 103 in the two-pinhole group. There were no statistically significant differences in baseline conditions such as gender, age, BMI, age of onset of PPH, hyperhidrosis sites, hyperhidrosis degree, and transection level of thoracic sympathetic chain between the two groups (P > 0.05). The two-pinhole group had shorter operation time (19.809 ± 3.356 min vs. 22.534 ± 4.541 min), lower postoperative incision pain score (1.563 ± 0.518 vs. 2.012 ± 0.788), and better incision satisfaction (9.437 ± 0.498 vs. 8.068 ± 1.424) (all P < 0.001). There were no statistically significant differences in postoperative conditions such as surgical effect, 24-h postoperative discharge rate, postoperative complication rate, postoperative compensatory hyperhidrosis, postoperative recurrence rate of PPH, and postoperative follow-up time between the two groups (P > 0.05).ConclusionThe ISTTST is a more concealed-scar, minimally invasive, and convenient procedure, meeting the aesthetic needs. Compared with the CSTTST, it has certain advantages and deserves more attention and attempts.